Interaction of PM2.5 and pre-pregnancy body mass index on birth weight: A nationwide prospective cohort study - Du, Hanze; Sun, Yuxin; Zhang, Yuelun; Wang, Shirui; Zhu, Huijuan; Chen, Shi; Pan, Hui (Frontiers in Endocrinology, 2022)
Background: Fine particulate matter (PM2.5) has been associated with many adverse birth outcomes in some studies. Pre-pregnancy body mass index (BMI) is an important indicator of maternal obesity that may also contribute to a wide range of birthweight outcomes. Both PM2.5 and maternal obesity have been found associated with issues on neonatal birthweight respectively, and more attentions and interests are focusing on their combined effect on pregnancy outcomes. Purpose: To explore the modifying effect of pre-pregnancy BMI on the association between gestational PM2.5 and birthweight; to investigate the interactive effect between gestational PM2.5 and pre-pregnancy BMI on birthweight among pregnant women during three trimesters and the whole pregnancy. Methods: This nationwide cohort study used the National Free Preconception Health Examination Project (NFPHEP) data collected from January 1, 2010, to December 31, 2012. A total population of 248,501 Chinese women from 220 counties registered this project. Pre-pregnancy BMI was collected during preconception investigation, and gestational PM2.5 was derived from a hindcast model for historical PM2.5 estimation from satellite-retrieved aerosol optic depth. Interaction analysis by introducing product terms to multivariable linear regression was also used to examine whether there was an interactive relationship between PM2.5 and pre-pregnancy BMI. Results: Totally, 193,461 participants were included in our study. The average concentration of PM2.5 was 75.33 μg/m3. Higher exposure of PM2.5 during the entire pregnancy was associated with higher birthweight 15.41 g per 10 μg/m3. Each 10 μg/m3 increase in PM2.5 during the first, second, and third trimesters was associated with increases in birthweight by 14.20 g , 12.78g, and 18.31 g. Higher pre-pregnancy BMI per kg/m2 was associated with an increase of birthweight by 7.012 g. Product terms between PM2.5 and pre-pregnancy BMI were significant for the first, second trimesters, and the entire duration of pregnancy. Conclusions: Our results found both PM2.5 and pre-pregnancy BMI respectively correlated with the increase of birthweight. A negative interaction between pre-pregnancy BMI and PM2.5 was discovered in term of birthweight gain. Avoidance of high-dose exposure to PM2.5 during the early and middle stages of pregnancy and pre-pregnancy overweight/obesity may help prevent high birthweight.